2001
DOI: 10.1073/pnas.051500898
|View full text |Cite
|
Sign up to set email alerts
|

Truncated hexa-octahedral magnetite crystals in ALH84001: Presumptive biosignatures

Abstract: McKay et al. [(1996)Science 273, 924 -930] suggested that carbonate globules in the meteorite ALH84001 contained the fossil remains of Martian microbes. We have characterized a subpopulation of magnetite (Fe3O4) crystals present in abundance within the Fe-rich rims of these carbonate globules. We find these Martian magnetites to be both chemically and physically identical to terrestrial, biogenically precipitated, intracellular magnetites produced by magnetotactic bacteria strain MV-1. Specifically, both magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 169 publications
(95 citation statements)
references
References 23 publications
2
93
0
Order By: Relevance
“…Greigite was never observed in magnetosomes. The specific crystal habit of magnetite is truncated hexaoctahedral, with eight 111 octahedral faces, six 110 hexagonal faces and six 100 cubic faces (Thomas-Keprta et al, 2001). The dimensions of each crystal are approximately 356 35653 nm, with the axis of elongation corresponding to the alignment of crystals within the chain (Fig.…”
Section: Cells Of Strain Mv-1mentioning
confidence: 99%
See 1 more Smart Citation
“…Greigite was never observed in magnetosomes. The specific crystal habit of magnetite is truncated hexaoctahedral, with eight 111 octahedral faces, six 110 hexagonal faces and six 100 cubic faces (Thomas-Keprta et al, 2001). The dimensions of each crystal are approximately 356 35653 nm, with the axis of elongation corresponding to the alignment of crystals within the chain (Fig.…”
Section: Cells Of Strain Mv-1mentioning
confidence: 99%
“…Strain MV -1 T has been the subject of several previous studies, centred mostly on the production and morphology of magnetite by this strain in culture (Bazylinski et al, 1988(Bazylinski et al, , 1995Thomas-Keprta et al, 2001;Dubbels et al, 2004), including the generation of spontaneous nonmagnetotactic mutants (Dubbels et al, 2004), and autotrophic growth of strain MV-1 T via the CalvinBenson-Bassham (CBB) cycle . Nevertheless, this important magnetotactic strain has not yet been characterized in the literature.…”
mentioning
confidence: 99%
“…Tooth-shaped Fe 3 S 4 crystals have also been observed 20 . Elongated crystals are so unusual that their presence in recent and ancient sediments and in the Martian meteorite ALH84001 has led to their designation as magnetofossils 115 , and is cited as evidence for the past presence of magnetotactic bacteria in aquatic habitats and sediments [115][116][117] and life on ancient Mars [118][119][120][121] . However, elongated crystals of and ELECTRON HOLOGRAPHY 44 (FIG.…”
Section: Magnetotaxismentioning
confidence: 99%
“…We have then used these new observations to evaluate the merits of both theoretical and experimental attempts to reproduce ALH84001-like disks with embedded magnetites through partial thermal decomposition of Fe-bearing carbonate. In the larger context, resolving or at least constraining the origin of the magnetites within ALH84001 carbonate disks has importance in that it has been previously suggested that the precipitation of the carbonate disks may have been facilitated through biogenic activity (McKay et al, 1996) and that a fraction of the embedded magnetites exhibit chemical and physical features identical to those produced by contemporary magnetotactic bacteria (McKay et al, 1996;Thomas-Keprta et al, 2000a;Thomas-Keprta et al, 2001;Thomas-Keprta et al, 2002). Table 1 lists the ALH84001 rock splits used in the research presented herein.…”
Section: Introductionmentioning
confidence: 99%